2015
DOI: 10.1080/00480169.2015.1034218
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of working dogs in New Zealand following pancarpal arthrodesis using dorsal hybrid plating

Abstract: Although this study has a small number of cases, this study provides subjective longer-term follow-up data than previously reported for working dogs that have undergone PCA. Owners should be warned that plate removal may be required in approximately 60% of dogs and additional expenditure should be planned for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In a study by Sawyere et al, infection or screw loosening was identified as the most common long-term complication necessitating implant removal following pancarpal arthrodesis. 19 Infection rates necessitating implant removal following pancarpal arthrodesis are difficult to accurately ascertain, 7,20-22 but have been reported as 7% in one study. 10 Implant removal precipitated by infection was predictable in dog 1, which had a chronically infected carpus, and in dog 2, which had chronic Staphylococcus pyoderma.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Sawyere et al, infection or screw loosening was identified as the most common long-term complication necessitating implant removal following pancarpal arthrodesis. 19 Infection rates necessitating implant removal following pancarpal arthrodesis are difficult to accurately ascertain, 7,20-22 but have been reported as 7% in one study. 10 Implant removal precipitated by infection was predictable in dog 1, which had a chronically infected carpus, and in dog 2, which had chronic Staphylococcus pyoderma.…”
Section: Discussionmentioning
confidence: 99%
“…Current treatment recommendations for multiligamentous carpal injuries include partial or pancarpal arthrodesis, even in the absence of hyperextension. 8,9 These invasive surgical procedures lead to the loss of the carpal range of motion or involve the risk of severe surgical complications, including surgical site infection, implant failure, metacarpal fractures and persistent lameness. 10 The most common reported complication was surgical site infection ranging between 18.3% and 31%.…”
Section: Outcome and Follow-upmentioning
confidence: 99%
“…Laterally, radioulnar (1), lateral collateral (2), short ulnar collateral (3), dorsal radiocarpal (4), and palmar ulnocarpal (9) ligaments were completely torn. Medially, the medial collateral (5), short radial collateral (6) ligaments and the short ligament(8) that is attached to the intermedioradial carpal bone and second carpal bone were ruptured. Entry points of the screws for lateral (yellow arrows) and medial ligament prosthesis (blue arrows) Abbreviations: CA, accessory carpal bone; CR, intermedioradial carpal bone; CU, ulnar carpal bone into the second carpal bone in a medial to lateral direction.…”
mentioning
confidence: 99%
“…Pancarpal arthrodesis involves surgical fusion of the antebrachiocarpal, middle carpal, and carpometacarpal joints. This surgical procedure is widely used to treat carpal hyperextension, regardless of the joint level involved, and it has yielded good results with refinement of the materials used for fixation 3–5 . Although pancarpal arthrodesis can improve gait to a satisfactory level, mechanical lameness can persist owing to the absence of a range of motion in the joints.…”
Section: Introductionmentioning
confidence: 99%
“…This surgical procedure is widely used to treat carpal hyperextension, regardless of the joint level involved, and it has yielded good results with refinement of the materials used for fixation. [3][4][5] Although pancarpal arthrodesis can improve gait to a satisfactory level, mechanical lameness can persist owing to the absence of a range of motion in the joints. Moreover, complications have been reported, including surgical site infection, plate fracture, screw loosening, and fracture of the bone adjacent to the plate.…”
Section: Introductionmentioning
confidence: 99%